Experimental investigation of the swirl effect on CAMPRO engine using designed swirl adapter - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur (2011)
Swirl is the rotational flow of charge within the cylinder about its axis. CAMPRO engine is a basic Double Overhead Camshaft (DOHC) which has a capacity of 1597 cc and installed with a total of 16 valves developed by Malaysian car manufacturer PROTON. The swirl adapter is theoretically placed inside the intake port of the CAMPRO Engine Model. The Adapter angle is set to 30o to force the charge to bounce off the wall of the port to create swirl. The objective of this paper is to find the effect of swirl on the engine and compare it to the normal turbulence mixing process. The swirl effect analysis is done by using the GT-SUITE which has a standard swirl flow embedded in the software. The effect is simulated on the GT-SUITE and it is found that the swirl affects the engine in reducing the fuel consumption and increasing the volumetric efficiency. The experimental result shows that the effect of swirl increases the power as well as torque in the idle and cruising speed condition in comparison with normal turbulence. But it decreases rapidly in the acceleration speed. This is because the swirl adapter is not able to generate swirl due to higher wind flow velocity at higher throttle opening condition.